2004
DOI: 10.1001/archsurg.139.11.1204
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Oximetry of Dyes Used for Sentinel Lymph Node Biopsy

Abstract: Hypothesis: There are differences between readings of peripheral blood oxygen saturation when the effect on saturation values of methylene blue is compared with that of isosulfan blue when used in sentinel lymph node biopsy in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
1
16
1
2
Order By: Relevance
“…Our findings were comparable to Pin) ero' s study, (14) which revealed no significant changes in oxy-…”
Section: Pulse Oximetry Is the Standard Methods For Non-inva-supporting
confidence: 91%
See 2 more Smart Citations
“…Our findings were comparable to Pin) ero' s study, (14) which revealed no significant changes in oxy-…”
Section: Pulse Oximetry Is the Standard Methods For Non-inva-supporting
confidence: 91%
“…Methylene blue theoretically is retained less and cleared more from the blood stream through the kidneys than isosulfan blue. (9,14,22) Scheller et al (9) reported that the peripheral pulse oximetry was transiently lowered among healthy volunteers who were injected intravenously with 5 mL of 1% methylene blue.…”
Section: Pulse Oximetry Is the Standard Methods For Non-inva-mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Furthermore, compared to the other dyes, methylene blue interferes less with oximetry. 24 Nevertheless, a case has been reported in the literature of a pulmonary edema possibly related to the use of methylene blue for the detection of the sentinel lymph node. 25 Another advantage of methylene blue is the possibility of being able to use it during pregnancy, which is not the case with the other dyes.…”
Section: Discussionmentioning
confidence: 99%
“…(12,13) There is also a controlled trial about the effects of methylene blue versus isosulfan blue usage in SNLB. (14) Pinero et al (14) compared isosulfan blue with methylene blue in 32 patients who were undergoing SLNB and obtained arterial blood samples for blood gas analysis but could not demonstrate any significant changes in blood gas analysis. On the other hand, the investigators did not state whether methemoglobin levels also included in this analysis or not.…”
Section: Discussionmentioning
confidence: 99%